2004
DOI: 10.1161/01.hyp.0000142772.71367.65
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Matrix Metalloproteinases and Collagens and Suppression of Cardiac Fibrosis by Inhibition of the Proteasome

Abstract: Abstract-Myocardial remodeling is an adaptive response of the myocardium to several forms of stress culminating in cardiac fibrosis, left ventricular dilation, and loss of contractility. The remodeling processes of the extracellular matrix are controlled by matrix metalloproteinases, which are in turn regulated by growth factors and inflammatory cytokines. The inflammatory transcription factor nuclear factor B has been implicated in the transcriptional regulation of several matrix metalloproteinases. Because a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 39 publications
8
63
1
1
Order By: Relevance
“…Activation of MMP-2 and 9 by IL-1β is consistent with previous reports in cardiac fibroblasts. [16][17][18] Additionally, our data directly demonstrate increased MMP-3 expression and activity, extending a previous observation of IL-1β induced increase in MMP-3 mRNA. [17] In contrast to that study, we observe no evidence for IL-1β activation of MMP-13.…”
Section: Discussionsupporting
confidence: 89%
“…Activation of MMP-2 and 9 by IL-1β is consistent with previous reports in cardiac fibroblasts. [16][17][18] Additionally, our data directly demonstrate increased MMP-3 expression and activity, extending a previous observation of IL-1β induced increase in MMP-3 mRNA. [17] In contrast to that study, we observe no evidence for IL-1β activation of MMP-13.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to bafilomycin A 1 , we observed that the inhibition of the proteasome by treatment with MG132 repressed the expression of Col-I ␣1 mRNA in MMC. Similar effect of MG132 has been previously reported in human dermal fibroblasts (43) and rat cardiac fibroblasts (44).…”
Section: Disruption Of Autophagic Activity Suppresses Intracellular Dsupporting
confidence: 88%
“…This negative regulatory effect of MG132, in fact, has been previously shown in human dermal fibroblasts (43) and rat cardiac fibroblasts (44). However the precise mechanism by which proteasome inhibitor MG132 represses Col-I ␣1 mRNA expression remains to be determined.…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that [19] in experimental inflammatory bo wel disease MG-132 in vivo reduced T cell-mediated intestinal inflammation but significantly suppressed cell migration and epithelial cell proliferation. MG-132 also has an influence on the cardiovascular system [8,29,34]. In a low dose (0.1 mg/kg) MG-132 administered intraperitoneally once per day even for 2 or 8 weeks may effectively prevent cardiac remodelling and dysfunction in pressure-overloaded hearts without marked drug toxicity [29].…”
Section: Systemic Administration Of Proteasome Inhibitionmentioning
confidence: 99%